Bispecific IgG neutralizes SARS-CoV-2 variants and prevents escape in mice - De Gasparo, Raoul; Pedotti, Mattia; Simonelli, Luca; Nickl, Petr; Muecksch, Frauke; Cassaniti, Irene; Percivalle, Elena; Lorenzi, Julio C C; Mazzola, Federica; Magrì, Davide; Michalcikova, Tereza; Haviernik, Jan; et al. (Nature, 2021)
Neutralizing antibodies that target the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein are among the most promising approaches against COVID-191,2. A bispecific IgG1-like molecule (CoV-X2) has been developed on the basis of C121 and C135, two antibodies derived from donors who had recovered from COVID-193. Here we show that CoV-X2 simultaneously binds two independent sites on the RBD and, unlike its parental antibodies, prevents detectable spike binding to the cellular receptor of the virus, angiotensin-converting enzyme 2 (ACE2). Furthermore, CoV-X2 neutralizes wild-type SARS-CoV-2 and its variants of concern, as well as escape mutants generated by the parental monoclonal antibodies. We also found that in a mouse model of SARS-CoV-2 infection with lung inflammation, CoV-X2 protects mice from disease and suppresses viral escape. Thus, the simultaneous targeting of non-overlapping RBD epitopes by IgG-like bispecific antibodies is feasible and effective, and combines the advantages of antibody cocktails with those of single-molecule approaches.
Keywords: Epitopes, B-Lymphocyte; modely nemocí na zvířatech; neutralizující protilátky; Immunoglobulin G; monoklonální protilátky; protilátky bispecifické; Dependovirus; Angiotensin-Converting Enzyme 2; COVID-19 Drug Treatment; imunoglobulin G; farmakoterapie COVID-19; Immune Evasion; imunitní únik; SARS-CoV-2; Body Weight; angiotensin-konvertující enzym 2; Animals; epitopy B-lymfocytární; lidé; Spike Glycoprotein, Coronavirus; ženské pohlaví; Humans; zvířata; Antibodies, Neutralizing; myši inbrední C57BL; Disease Models, Animal; myši; Antibodies, Bispecific; Mice, Inbred C57BL; Antibodies, Monoclonal; Mice; Female; tělesná hmotnost; glykoprotein S, koronavirus; COVID-19